Impact Evaluation of a Parolee-Based Focused Deterrence Program on Community-Level Violence - Clark-Moorman, Kyleigh (Criminal justice policy review, 2019)
We estimate the impact of a parolee-based focused deterrence (“pulling levers”) intervention on community-level firearm and non-firearm violence in Rockford, Illinois, via a retrospective, quasi-experimental design. Focusing on incidents of firearm violence in Rockford over a period of 60 months (38 months pre-intervention, 22 months post-intervention), program impact is assessed using Bayesian Structural Time Series (BSTS) models, constructing a synthetic control-based counterfactual time series from National Incident-Based Reporting System (NIBRS) data from 59 non-treated cities of similar size. Relative to the synthetic control counterfactual, the intervention was associated with significant reductions in both firearm and non-firearm violence, particularly robberies, ranging from 6% to 30%. Consistent with research at other sites, these findings support the notion that focused deterrence strategies centered on high-risk parolees may result in reductions in firearm violence at the community level. The BSTS approach is a useful application for producing counterfactuals in retrospective quasi-experimental impact evaluations.